2011
DOI: 10.1016/j.neuron.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Plk2 in Orchestrated Ras and Rap Signaling, Homeostatic Structural Plasticity, and Memory

Abstract: Summary Ras and Rap small GTPases are important for synaptic plasticity and memory. However, their roles in homeostatic plasticity are unknown. Here, we report that polo-like kinase 2 (Plk2), a homeostatic suppressor of overexcitation, governs the activity of Ras and Rap via coordination of their regulatory proteins. Plk2 directs elimination of Ras activator RasGRF1 and Rap inhibitor SPAR via phosphorylation-dependent ubiquitin-proteasome degradation. Conversely, Plk2 phosphorylation stimulates Ras inhibitor S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
118
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 45 publications
3
118
0
Order By: Relevance
“…We found that a major downstream function of Plk2 is to orchestrate Ras and Rap signaling 26 -not by targeting just one regulator, but four of them. Interaction and kinase assays demonstrated that Plk2 directly binds to and phosphorylates both a GAP and a GEF for Rap (the proteins SPAR and PDZGEF1, respectively), as well as a GAP and a GEF for Ras (SynGAP and RasGRF1).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…We found that a major downstream function of Plk2 is to orchestrate Ras and Rap signaling 26 -not by targeting just one regulator, but four of them. Interaction and kinase assays demonstrated that Plk2 directly binds to and phosphorylates both a GAP and a GEF for Rap (the proteins SPAR and PDZGEF1, respectively), as well as a GAP and a GEF for Ras (SynGAP and RasGRF1).…”
Section: Introductionmentioning
confidence: 87%
“…3,24 Moreover, the balance between Ras and Rap activities also seems to be a critical parameter, not merely their individual levels. 25 Thus, as discussed in further detail in the next section, our recent study 26 has sought to analyze Ras and Rap regulation in a more surgical manner via manipulation of specific Ras and Rap GAPs/GEFs. This approach has also allowed us to ask whether coordinated Ras/Rap signaling is important for one form of homeostatic plasticity, adaptation to chronic synaptic overexcitation.…”
Section: Introductionmentioning
confidence: 99%
“…Plks regulate the cell cycle and cytokinesis in dividing cells, whereas their function in nondividing cells, such as neurons, is less well understood. Recent studies have shown that in neurons, Plk2 regulates the activity of two small guanosine triphosphatases (GTPases), Ras and Rap, by phosphorylating their activators (GEFs, guanine nucleotide exchange factors) and inactivators (GAPs, GTPase-activating proteins) (12,13). In yeast, Cdc5 also regulates the activity of the small GTPase Rho1 by phosphorylating its GEFs (Tus1 and Rom2) and GAP (Sac7) (14).…”
mentioning
confidence: 99%
“…For example, reduced MECP2, downregulated in this study, has been previously shown to decrease the number of synapses formed, lead to a reduction in synaptic response and an increased retraction of dendrites (Chao et al, 2007;Nguyen et al, 2012). Furthermore, reductions in APP, MECP2, PPFIA3 and RASGRF1, all proteins down-regulated in the proteomics, have previously been reported to reduce synaptic plasticity (Schoch et al, 2002;Moretti et al, 2006;Tomiyama et al, 2010;Lee et al, 2011).…”
Section: Synaptic Plasticitysupporting
confidence: 52%